Framing a Vision of the World - Sia, Santiago (eds) (Louvain Philosophical Studies, 1999)
In October 1998 prof. Jan Van der Veken retired as professor of metaphysics and philosophy of God at the Katholieke Universiteit Leuven, after more than thirty years of teaching. For a long time he was one of the driving forces behind the Institute of Philosophy's flourishing International Program. He is also the president of the European Society for Process Thought and Director of the Process Documentation Center in Leuven. Because of his broad international commitment, colleagues, friends and former Ph.D-students from all over the world are offering him this collection of essays, which reflect his areas of interest, as a tribute to his work and career. Since for Jan Van der Veken our vision of the world, and especially the placing of God and religion in it, has been the basic concern in all his work and thought, this problem is also at the core of this volume. Though religion, philosophy and science speak different languages, it is the task of our vision of the world to bring them into some rational coordination. Many philosophers have guided him in this intellectual search. The first of these has been the later Merleau-Ponty, on whose philosophy he wrote his doctoral dissertation and who has remained present in his thinking. But the discovery of the work of Charles Hartshorne and Alfred North Whitehead opened up for him completely new perspectives and provided him with a new tool to formulate his own insights. It may be said that Jan Van der Veken introduced process-thought in the Low Countries, and that he is still its main proponent. All these aspects of Jan Van der Veken's thought are treated in this volume. All the contributions testify to the breath of interest, so characteristic of Jan Van der Veken's thinking but also of the necessity of an over-all vision of the world. In an Postscript, Jan Van der Veken himself reconstructs his own journey from Being to Becoming.